Echo ebook - Ryan, Pam Muñoz (2015)
Newbery Honor Book New York Times Bestseller This impassioned, uplifting, and virtuosic tour de force from a treasured storyteller follows three children, in three different times and places, whose lives mysteriously intersect. Lost and alone in a forbidden forest, Otto meets three mysterious sisters and suddenly finds himself entwined in a puzzling quest involving a prophecy, a promise, and a harmonica. Decades later, Friedrich in Germany, Mike in Pennsylvania, and Ivy in California each, in turn, become interwoven when the very same harmonica lands in their lives. All the children face daunting challenges: rescuing a father, protecting a brother, holding a family together. And ultimately, pulled by the invisible thread of destiny, their suspenseful solo stories converge in an orchestral crescendo. Richly imagined and masterfully crafted, Echo pushes the boundaries of genre, form, and storytelling innovation to create a wholly original novel that will resound in your heart long after the last note has been struck.